Socioeconomic Status and Psychological Distress among Urban and Rural Dwellers in Ghana - Opuni, K. (University of Ghana, 2023)
Socioeconomic status (SES) plays a pivotal role in determining the opportunities, challenges, and life trajectories of people globally. Socioeconomic status factors, such as educational attainment, the type of occupation, and subjective social status of an individual, significantly impact their overall well-being. Studies examining the relationship between individuals' SES and overall psychological well-being have gained considerable attention in Ghana. However, previous studies investigating the association between SES and individuals' psychological well-being have predominantly utilised cross-sectional methodologies. Previous research utilising longitudinal methods to examine the relationship between socioeconomic status (SES) and psychological well being has primarily concentrated on the influence of individual-level SES and other personal variables on psychological well-being. However, these studies have failed to account for the potential impact of household and community factors on psychological well-being. This study sought to present empirical evidence on the effects of an individual’s SES, and other personal and external factors on their psychological well-being over time. This study employed quantitative and qualitative designs using the sequential explanatory mixed-method approach to provide answers to the research questions. The quantitative data for this study was derived from the first three waves of the Ghana socioeconomic Panel Survey (GSPS) conducted by the Institute of Statistical, Social and Economic Research (ISSER), University of Ghana and the Global Poverty Research Lab (GPRL) at Northwestern University, USA. The total sample size for the quantitative data for the study was 25,924 individual participants aged 18 years and older who had participated in the three waves. The qualitative stage encompassed the implementation of focus group discussions (FGDs) across specific urban and rural locations spanning the three ecological zones of Ghana. Twelve (12) FGDs were conducted in six communities- one male and one female per community. The quantitative data was analysed using cross-sectional panel descriptive statistics and multivariate panel regression models with pooled ordinary least squares (OLS), fixed, and random effects specifications. The interviews were audio-taped from FGDs, transcribed, and analysed using content analysis. The study found that the prevalence of psychological distress was higher among respondents residing in rural areas (66.1%) than those living in urban areas (52.9%). In the multivariate analysis, the study observed a negative correlation between educational attainment and psychological distress. Specifically, individuals in urban areas without any educational qualifications or with lower educational qualifications exhibited higher levels of psychological distress compared to those who had obtained a bachelor's degree or higher. However, no significant association was found between educational attainment and psychological distress in rural locations. At the household level, the study found that respondents with higher wealth quintiles, those who did not have any household debt and did not receive any transfer of goods or money from people outside of their household experienced lower levels of psychological distress. The study also discovered that at the community level, in both urban and rural areas, respondents’ perceptions of the helpfulness of community members lessened the likelihood of experiencing psychological distress. The study’s findings revealed an overall prevalence of psychological distress among participants residing in urban and rural areas in Ghana. In addition, psychological distress over time was found to be significantly predicted by lower educational qualification attainment in Ghana. The study recommends the establishment of voluntary psychological distress screening centres.
PhD. Population Studies
Keywords: Socioeconomic status (SES); Ghana; psychological well-being